Using by-products for rehabilitating mine sites or degraded lands: systematic review and meta-analysis on phosphogypsum, phosphate sludge and sewage sludge - Guéablé, Yao Kohou Donatien; Bohoussou, N’Dri Yves; El Gharous, Mohamed; El Mejahed, Khalil; Hafidi, Mohamed (Frontiers in Environmental Science, 2025)
Phosphogypsum (PG), phosphate sludge (PS), and sewage sludge (SS) are regarded by-products produced in huge amounts. However, PG, PS and SS are no longer considered as waste, but as valued resources in accordance with the circular economy's rules. Their management provides a serious environmental problem. In order to assess the impacts of SS, PS, and PG on soil physico-chemical parameters (pH, EC, OM, nutrients, and heavy metals) in response to diverse experimental settings, the purpose of the current study was to conduct a meta-analysis on previously published results. The VOSviewer program was used to construct bibliometric maps using the VOS mapping and grouping techniques. The findings indicated that there were statistically significant changes (P < 0.05) in electrical conductivity (EC), organic matter (OM), and pH in connection to the different by-products employed. The application of SS considerably elevated pH by 46.15% compared to the control. Furthermore, a beneficial effect on P and K was detected, regardless of the by-product used. Moreover, Cd, Pb, and Ni concentrations in SS treatments had a substantial reduction of 30.46%, 30.70%, and 18.07%, respectively. Cd, Pb, and Cu concentrations in PG treatments revealed a substantial decrease of 47.71%, 36.14%, and 46.01%, respectively. Based on the acquired data, PG, PS, and SS need to be regularly monitored and regulated. This study serves as an early investigation for the construction of a new approach to restore damaged land on mine sites by employing phosphate industry by-products and sludge for revegetation objectives.